2012
DOI: 10.2320/matertrans.m2012170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium and Aluminum Oxides on Fluidity of Final Blast Furnace Slag and Its Application

Abstract: Generally, decreasing slag volume of blast furnace operation can lead to the lower fuel ratio and higher productivity. For high sinter ratio operation, one of effective ways to obtain a lower slag volume is to reduce the gangue content of sinter. Basically, lowering the amount of serpentine in the sinter mix is a feasible way to produce suitable sinter with the lower gangue content. However, this method may result in lower magnesium oxide content in the final slag that may affect its fluidity. Hence, the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…The isoviscosity curves become closer and closer as the temperatures decrease and the Al 2 O 3 content increases, which indicates that the thermal stability of slag start to deteriorate with the Al 2 O 3 content increased and the temperatures decreased and that Al 2 O 3 has a more obviously influence on the slag viscosity at high Al 2 O 3 concentration. Similar to previous studies, [20,28] Al 2 O 3 additions resulted in an increase in viscosity at a fixed temperature. Especially at lower temperature, the values rise sharply with Al 2 O 3 content.…”
Section: Methodssupporting
confidence: 90%
“…The isoviscosity curves become closer and closer as the temperatures decrease and the Al 2 O 3 content increases, which indicates that the thermal stability of slag start to deteriorate with the Al 2 O 3 content increased and the temperatures decreased and that Al 2 O 3 has a more obviously influence on the slag viscosity at high Al 2 O 3 concentration. Similar to previous studies, [20,28] Al 2 O 3 additions resulted in an increase in viscosity at a fixed temperature. Especially at lower temperature, the values rise sharply with Al 2 O 3 content.…”
Section: Methodssupporting
confidence: 90%
“…MgO has an essential influence on the BF iron‐making process, and the appropriate MgO content is suggested to gain an optimal softening–melting property and a fluid slag. It is reflected in the positive influence that MgO content had on the liquidity, stability, and desulfurization ability of the BF slag and the properties of sinter . The liquidity, desulfurization, and dealkalization capacities of the slag could be improved by using a high MgO content of sinter in the BF.…”
Section: Introductionmentioning
confidence: 99%
“…mended in a range of 0.6-0.7 in the high Al 2 O 3 content. Shiau et al 4) indicated that the lower liquidus temperature and the better viscosity stability laid in the area of MgO = 5.4 wt%, Al 2 O 3 = 10-15 wt%, and C/S (CaO/SiO 2 ) = 1.2. Lu et al 5) investigated that the viscosity and the melting temperature of the slag.…”
Section: Operation Characteristic Of Super-large Blast Furnace Slag Imentioning
confidence: 99%
“…Jiao KEXIN, 1,3) * Zhang JIANLIANG, 1,2) Chen CHUNLIN, 3) Liu ZHENGJIAN 1,2) and Jiang XI 4) Operational smoothly of ironmaking process is determined to a great extent by its slag performance especially for the large blast furnace. Operation characteristic of super-large blast furnace slag in China was summarized and the appropriate adjustment measures for better performance of BF were analyzed based on the operation characteristic by using the MPE.…”
Section: Operation Characteristic Of Super-large Blast Furnace Slag Imentioning
confidence: 99%